1980
DOI: 10.1017/s0033291700054933
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of children with head injuries: I. Design and methods

Abstract: SYNOPSISThe main unresolved issues with respect to the psychological sequelae of brain damage in childhood are noted, and the previous studies of children suffering head injury are critically reviewed. A new prospective study is described. Three groups of children were studied: (a) 31 children with ‘severe’ head injuries resulting in a post-traumatic amnesia of at least 7 days; (b) an individually matched control group of 28 children with hospital-treated orthopaedic injuries; and (c) 29 children with ‘mild’ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…However, in 40% of the children improvement on the cognitive domains was found even years after rehabilitation. Others also found that improvement after TBI is possible [7,13,38,41,42]. Improvement was mostly found on the intelligence scales and on the attention assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 40% of the children improvement on the cognitive domains was found even years after rehabilitation. Others also found that improvement after TBI is possible [7,13,38,41,42]. Improvement was mostly found on the intelligence scales and on the attention assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Spina Bifida, Cerebral Palsy or Autism), pre-injury diagnosis of mental retardation or prior brain injury were excluded from this study. Children were not excluded for pre-injury learning or behaviour problems in order to increase the generalizability of findings to the paediatric TBI population, which has been demonstrated to have an increased incidence of these problems [57,58]. Demographic and injury-related information are summarized in Tables I and II.…”
Section: Participantsmentioning
confidence: 99%
“…In particular, falls from tower blocks onto concrete as well as falls at home while playing have been common (Field, 1979). Other causes of HI in children have included injuries during accidents and child abuse (Jennett, 1972;Rutter, Chadwick, Shaffer, & Brown, 1980). In fact, child abuse has been found to be a main cause of HI in infants less than 1 year old (LangeCosack & Tepfer, 1973).…”
Section: Etiology and Risk Factors Associated With Hismentioning
confidence: 99%